Efficacy and safety of ultrasound-guided microwave ablation versus surgical resection for Bethesda category IV thyroid nodules: A retrospective comparative study - Yang, Jingjing; Zhang, Ya; Li, Xingjia; Zhao, Yueting; Han, Xue; Chen, Guofang; Chu, Xiaoqiu; Li, Ruiping; Wang, Jianhua; Huang, Fei; Liu, Chao; Xu, Shuhang (Frontiers in Endocrinology, 2022)
Abstract Objective: The objective of this study was to assess the efficacy and safety of ultrasound-guided microwave ablation (MWA) for Bethesda IV thyroid nodules, and to compare the outcomes, complications, and costs of MWA and thyroidectomy. Methods: A total of 130 patients with Bethesda IV nodules were retrospectively reviewed, involving 46 in MWA group and 84 in surgery group. The local institutional review board approved this study. Patients in MWA group were followed up at 1, 3, 6 and 12 months after intervention. Postoperative complications, treatment time and cost in two groups were compared. Results: Among 84 patients with 85 Bethesda IV nodules in surgery group, postoperative pathology was benign lesions, borderline tumors, papillary thyroid carcinoma, follicular variant papillary thyroid carcinoma, follicular thyroid carcinoma, medullary carcinoma, 44 cases, 4 cases, 27 cases, 6 cases, 3 cases, 1 case, respectively. . Malignant thyroid nodules were more prone to solid echostructure (86.11% vs. 72.72%), hypoechogenicity (55.56% vs. 13.63%) and irregular margin (47.22% vs. 13.63%) than benign lesions. The nodule volume reduction rate of patients at 12 months after MWA was 85.01±10.86%. Recurrence, lymphatic and distant metastasis were not reported during the follow-up period. The incidence of complications, treatment time, hospitalization time, incision length and cost were significantly lower in MWA group than in surgery group (all P<0.001). Conclusions: MWA significantly reduces the volume of Bethesda IV nodules with a high safety and is recommended to those with surgical contraindications or refusing surgical resection. Patients with suspicious ultrasound features for malignancy should be actively treated with surgery.